(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Given the establishment of new journals as a way to fill in gaps and further studies in the area of Knowledge Management and the impact Knowledge Management has had for two decades as a tool for competitive advantage, the aim of the study was to point out tendencies and discuss academic production in Knowledge Management over the years. As the focus of discussion, the article analyzes the relationship of Knowledge Management between Innovation Management, Technology Management and Information Management. The source material for mapping academic output was ten international journals, which were selected from 2006 to 2012, obtaining an initial sample of 2,900 papers. The systematic search was conducted to identify which relationships are more predominant in the journals selected. Through the analysis of relationships in publications within the time interval established, it was found that the relationship between Knowledge Management and Technology Management appears much more frequently in all publications over the years. The relationship between Knowledge Management and Technology Management decreased significantly in recent years. In contrast, there was an increase in papers discussing Knowledge Management and Innovation Management. Keywords: Information management. Innovation management. Knowledge management. Technology management. Link para o texto completo (PDF) http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/article/view/1957/1753